Effect of controlled-release chlorine dioxide on the quality and safety of cherry/grape tomatoes. (December 2017) - Sun, Xiuxiu; Zhou, Bin; Luo, Yaguang; Ference, Christopher; Baldwin, Elizabeth; Harrison, Ken; Bai, Jinhe
Abstract: The effect of controlled-release chlorine dioxide (ClO2 ) gas on the food safety and quality of cherry/grape tomatoes was investigated. Whole grape tomatoes artificially inoculated with either Escherichia coli or Alternaria alternata, or whole cherry tomatoes inoculated with Salmonella enterica Newport, were packed in 1-lb clamshells, and stored at 20 °C for 14 days. ClO2 pouches were attached under the lids with the following four dosages/release rates: single dose slow-release (S), single dose fast-release (F), fast/slow-release combination (FS), and double dose fast-release (FF). The corresponding equilibrium ClO2 concentration in the headspace was about 2, 4, 6 and 8 ppm, respectively. Treatment with F reduced populations of E. coli and A. alternata by 2.9–4.7, and 1.6 to 4.0 log CFU/g, respectively, within 14 days storage at 20 °C. FS and FF treatments showed little benefit over F. The F and FF treatments reduced population of S. enterica for inoculated cherry tomatoes by 3.28 and 3.80 log CFU/g, respectively, compared to control after 14 days' storage at 20 °C. ClO2 -treated grape tomatoes retained higher firmness and had less weight loss compared to the control. The results indicate that 2 ppm of ClO2 (S) in the clamshells did not adequately control microbial populations; the minimum effective concentration of ClO2 was 4 ppm (F). Higher concentrations provided a small but incremental improvement in ability to control microorganisms. ClO2 released into packages of cherry tomatoes during storage reduced weight loss, while maintaining firmness. Highlights: Controlled-release ClO2 pouch in clamshell showed antimicrobial activity in grape/cherry tomatoes. A minimum dosage of ClO2, 4 ppm in the headspace was determined in packaged fruits. Escherichia coli, Alternaria alternata, and Salmonella enterica, all responded to ClO2 treatments. Controlled-release ClO2 pouch also reduced fruit weight loss and softening in grape tomatoes.